Image technology: state of the art - Dailey, Franklyn E. (Computer Technology Research Corp. CharlestonUS, 1992)
Examines document applications developed specifically from image technology. Reviews some of the relationships between applications of document image management and other electronic imaging technologies. covers the stimulus of technology as well as some of the reasons that document management applications have been shown to develop.